Conjugated polymers mediate intracellular Ca2+ signals in circulating endothelial colony forming cells through the reactive oxygen species-dependent activation of Transient Receptor Potential Vanilloid 1 (TRPV1). (January 2022) - Negri, Sharon; Faris, Pawan; Tullii, Gabriele; Vismara, Mauro; Pellegata, Alessandro F.; Lodola, Francesco; Guidetti, Gianni; Rosti, Vittorio; Antognazza, Maria Rosa; Moccia, Francesco
Highlights: Optical excitation of rr-P3HT thin films induces a long-lasting increase in [Ca 2+ ]i in circulating endothelial colony forming cells (ECFCs). The Ca 2+ response to light is triggered by TRPV1 and requires the engagement of InsP3 receptors and store-operated Ca 2+ entry. TRPV1 is gated by hydrogen peroxide produced at the interface between the cell membrane and photosensitive nanomaterial upon light stimulation. TRPV1 may serve as a decoder at the interface between rr-P3HT thin films and ECFCs to translate optical excitation in pro-angiogenic Ca 2+ signals. Abstract: Endothelial colony forming cells (ECFCs) represent the most suitable cellular substrate to induce revascularization of ischemic tissues. Recently, optical excitation of the light-sensitive conjugated polymer, regioregular Poly (3-hexyl-thiophene), rr-P3HT, was found to stimulate ECFC proliferation and tube formation by activating the non-selective cation channel, Transient Receptor Potential Vanilloid 1 (TRPV1). Herein, we adopted a multidisciplinary approach, ranging from intracellular Ca 2+ imaging to pharmacological manipulation and genetic suppression of TRPV1 expression, to investigate the effects of photoexcitation on intracellular Ca 2+ concentration ([Ca 2+ ]i ) in circulating ECFCs plated on rr-P3HT thin films. Polymer-mediated optical excitation induced a long-lasting increase in [Ca 2+ ]i that could display an oscillatory pattern at shorter light stimuli. Pharmacological and genetic manipulation revealed that the Ca 2+ response to light was triggered by extracellular Ca 2+ entry through TRPV1, whose activation required the production of reactive oxygen species at the interface between rr-P3HT and the cell membrane. Light-induced TRPV1-mediated Ca 2+ entry was able to evoke intracellular Ca 2+ release from the endoplasmic reticulum through inositol-1, 4, 5-trisphosphate receptors, followed by store-operated Ca 2+ entry on the plasma membrane. These data show that TRPV1 may serve as a decoder at the interface between rr-P3HT thin films and ECFCs to translate optical excitation in pro-angiogenic Ca 2+ signals. Graphical abstract: Image, graphical abstract